What was Killing Babies in Rostock? An Investigation of Infant Mortality Using Individual-Level Cause-of-Death Data, 1800–1904 - Michael Mühlichen; Laura Ann Cilek (Historical Life Course Studies)
This paper examines the causes of infant mortality for the Hanseatic city of Rostock, Germany, between 1800 and 1904. Based on unique individual-level church records from Rostock's largest inner-city parish, St. Jakobi, we apply the novel ICD10h coding system for the first time to the German context. Using this coding system, we analyse cause-specific patterns of infant, neonatal and post-neonatal mortality in an internationally comparable way and bring new insights into the determinants of 19th-century infant mortality, which was shaped by increase and stagnation in wide parts of Germany. Our results show that Rostock experienced a stagnating infant mortality rate at a low level in international comparison during the first 40 years of the 19th century, followed by severe increases during the next 20 years and a stage of slight decline and stagnation towards the end of the study period. This suboptimal development from 1840 was strongly related to post-neonatal mortality and causes of death that are related to unfavourable sanitary conditions and/or poor nutrition, which possibly hints at worsening housing and living conditions following accelerated population growth. Our analyses also reveal that water-food borne diseases were underestimated in Rostock, even though symptomatic disease terms such as convulsions and teething, that were frequently recorded over much of the 19th century, had deviating seasonality patterns and thus cannot entirely refer to this disease group but rather to a wide field of different diseases. The applied coding scheme is a significant step forward to foster comparative international research on historical cause-specific mortality.